BUILDING UP THE COMMON EUROPEAN VALUES IN PROFESSIONAL TRAINING OF FUTURE FOREIGN LANGUAGE TEACHERS - Goncharova, Olga; Maslova, Alina (Studies in Comparative Education, 2022)
Ukraine is now on the threshold of entering the European Union, which affects all the life spheres and education in particular. The article deals with analyzing the common European values in terms of their introduction to the teacher training system in Ukraine. The authors draw attention to the issue of multilingualism which enhances learning foreign languages, helps to protect Europe’s rich linguistic diversity, and improves the competitiveness of the EU economy. As a result of the theoretical analysis, the authors conclude that building up the EU common values and incorporating them into the process of future foreign language teachers' training is a lifelong process that demands daily and ongoing work as teachers should put much effort into organizing the appropriate educational context and make a new generation of children raised in Ukraine not only feel European but act according to European values. The article also provides the results of the survey that, on the one hand, show that future foreign language teachers are not aware enough of the European policy of multilingualism as well as common European values. On the other hand, students realize the necessity of integrating Ukraine into the European educational environment and the importance of foreign language learning and teaching. The obtained results emphasize the necessity of introducing the Module on “Strengthening the EU common values through the policy of multilingualism in the education and training of future teachers” into the university's educational process.